The Influence of Job Satisfaction, Job Stress, and Burnout on Turnover Intentions of Generation Z Employees in the Jakarta Banking Sector: Mediated by Organizational Commitment - Albarazi, M. Zein; Handoyo, Sarwo Edy (Jurnal Ilmiah Sumber Daya Manusia, 2025)
In the era of globalization marked by increasingly complex work dynamics, the issue of turnover intentions has become a serious concern, especially in the banking sector. Generation Z, which is starting to dominate the workforce, has different characteristics and work expectations compared to previous generations, thus requiring a more adaptive HR management approach. This study aims to examine the effect of job satisfaction, job stress, and burnout on turnover intentions of Generation Z employees in the banking sector in Jakarta, with organizational commitment as a mediating variable. The findings of this study are expected to contribute to formulating more effective employee retention strategies amidst the challenges of global competition and changes in workforce characteristics. However, this study also provides insights relevant to understanding turnover intentions, particularly in the context of Generation Z employees in the Jakarta banking sector, where job satisfaction, job stress, and burnout play a significant role. The research utilizes the Structural Equation Modeling (SEM) approach with Partial Least Squares (PLS) analysis using SmartPLS 3.0 software. The findings indicate that leadership, motivation, and work environment significantly and positively affect employee performance. These findings are relevant to the broader framework of turnover intentions, where organizational commitment can serve as a mediating variable. The study contributes to human resource management practices by highlighting the importance of internal organizational factors that influence not only performance but also employee retention. Organizations are encouraged to develop supportive leadership, improve motivation strategies, and create a conducive work environment to reduce stress and burnout while increasing job satisfaction and commitment among Generation Z employees. These efforts are particularly important in the competitive and dynamic banking industry, where talent retention is critical for long-term success.